Age‐adjusted mortality and predictive value of liver chemistries in a Viennese cohort of COVID‐19 patients. (5th May 2022) - Hartl, Lukas; Haslinger, Katharina; Angerer, Martin; Jachs, Mathias; Simbrunner, Benedikt; Bauer, David J. M.; Semmler, Georg; Scheiner, Bernhard; Eigenbauer, Ernst; Strassl, Robert; Breuer, Monika; Kimberger, Oliver; et al.
Abstract: Background and Aims: The coronavirus disease of 2019 (COVID‐19) causes considerable mortality worldwide. We aimed to investigate the frequency and predictive role of abnormal liver chemistries in different age groups. Methods: Patients with positive severe acute respiratory distress syndrome‐coronavirus‐2 (SARS‐CoV‐2) polymerase chain reaction (PCR) test between 03/2020‐07/2021 at the Vienna General Hospital were included. Patients were stratified for age: 18–39 vs. 40–69 vs. ≥70 years (y). Aspartate aminotransferase (AST), alanine‐aminotransferase (ALT), alkaline phosphatase (ALP), gamma‐glutamyl transferase (GGT) and total bilirubin (BIL) were recorded. Results: 900 patients (18–39 years: 32.2%, 40–69 years: 39.7%, ≥70 years: 28.1%) were included. Number of comorbidities, median D‐dimer and C‐reactive protein increased with age. During COVID‐19, AST/ALT and ALP/GGT levels significantly increased. Elevated hepatocellular transaminases (AST/ALT) and cholestasis parameters (ALP/GGT/BIL) were observed in 40.3% ( n = 262/650) and 45.0% ( n = 287/638) of patients respectively. Liver‐related mortality was highest among patients with pre‐existing decompensated liver disease (28.6%, p < .001). 1.7% of patients without pre‐existing liver disease died of liver‐related causes, that is consequences of hepatic dysfunction or acute liver failure. Importantly, COVID‐19‐associated liver injury (16.0%, p < .001), abnormal liver chemistries and liver‐related mortality (6.5%, p < .001) were most frequent among 40–69 years old patients. Elevated AST and BIL after the first positive SARS‐CoV‐2 PCR independently predicted mortality in the overall cohort and in 40–69 years old patients. Conclusions: Almost half of the COVID‐19 patients exhibit abnormal hepatocellular and cholestasis‐related liver chemistries with 40–69 years old patients being at particularly high risk for COVID‐19‐related liver injury and liver‐related mortality. Elevated AST and BIL after SARS‐CoV‐2 infection are independent predictors of mortality, especially in patients aged 40–69 years.